2016
DOI: 10.1002/cbin.10636
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of stomatin causes syncytium formation in nonfusogenic JEG‐3 choriocarcinoma placental cells

Abstract: Placental trophoblast differentiation involves the continuous fusion of mononuclear cytotrophoblasts. However, except for syncytin, little is known about the detailed mechanisms underlying trophoblast fusion. A previous study indicated that lipid rafts play an important role in HTLV-1 syncytium formation. To identify proteins that may be involved in placental trophoblast differentiation, we examined stomatin, an important lipid-raft protein that localizes to detergent-resistant membrane domains. The syncytium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Similarly, in neutrophils, stomatin is associated with azurophil granules, but also other specific granules [13], and is likewise relocated to the plasma membrane upon activation [1]. Stomatin is also expressed in placental cells, where it may play an important role in trophoblast differentiation [14], and in bone, where it promotes osteoclastogenesis [15]. Trafficking of stomatin to the plasma membrane appears to follow the Golgi-pathway [16], while endocytosis most probably follows a clathrin-independent endocytosis pathway similar to caveolin-1 [17] and flotillins [18].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in neutrophils, stomatin is associated with azurophil granules, but also other specific granules [13], and is likewise relocated to the plasma membrane upon activation [1]. Stomatin is also expressed in placental cells, where it may play an important role in trophoblast differentiation [14], and in bone, where it promotes osteoclastogenesis [15]. Trafficking of stomatin to the plasma membrane appears to follow the Golgi-pathway [16], while endocytosis most probably follows a clathrin-independent endocytosis pathway similar to caveolin-1 [17] and flotillins [18].…”
Section: Introductionmentioning
confidence: 99%
“…19 Studies found that stomatin and its family members participate in the occurrence of malignant tumors, and that SLP-2 is overexpressed in choriocarcinoma placental cells, ovarian cancer, and cervical cancer; however, research on SLP-2 in liver cancer is rarely conducted. [20][21][22] We found for the first time that inhibiting the expression of SLP-2 gene in liver cancer cells could inhibit NF-kB, reduce the inflammatory response, and downregulate the expression levels of MMP-2 and MMP-9 and therefore inhibit the migration and invasion of liver cancer cells. 23 The purpose of this study was to investigate the effect of SLP-2 on liver cancer cells, and the data showed that the expression level of SLP-2 gene in liver cancer cells was higher than that in human normal liver cells, suggesting that SLP-2 is possibly involved in the growth of hepatoma cells.…”
Section: Discussionmentioning
confidence: 88%
“…Novel functional roles of stomatins have been implicated in over-expression analysis. In humans, over-expression of STOM and SLP-1 implicated roles in placental trophoblast differentiation and protein trafficking, respectively [ 31 , 48 ]. Also, SLP-2 over-expression was associated with several clinicopathological features in thyroid cancer patients [ 49 ].…”
Section: Resultsmentioning
confidence: 99%